Kontroverse um Grundtvig und Kierkegaard I - I I - Toftdahl, Hellmut (Grundtvig-studier, 1971)
Kontroverse um Kierkegaard und Grundtvig l - I I Reviewed by Hellmut Toftdahl Up till now the two first volumes of this three volume series have been published. The series was occasioned by a Dano-German conference of theologians at Båring Folk High School in the autumn of 1964 headed by professor Götz Harbsmeier from Göttingen. During the conference the Germans were introduced to Kaj Thaning’s Grundtvig and K. E. Løgstrup’s critique of Kierkegaard.The main study in vol. I is a summary of the main trend in Thaning’s thesis for the doctorate, ‘ Menneske først Christianity frees man from the responsibility of having to transform himself; instead it is his duty to lead the life of a natural human being. This instance of secularisation must have a highly promising ring to German ears, familiar as they are with the Catholic tendency to seeing the value of human life from a purely religious point of view, and the endeavours to subordinate all aspects of life under the guardianship of the church. A word of warning against Thaning’s one-sidedness is called for, however. The tolerance that Grundtvig showed after 1830 was dependent on his firm belief that man had been ‘created’, that he was ‘a divine experiment’, and that the link between God and man was beyond dispute. If the validity of this organic link was questioned—and this is what Grundtvig believed Kierkegaard to have done—then he had to condemn such questions. Seen from Kierkegaards’ sceptical point of view, Grundtvig’s congregational cult of baptism and Holy Communion is an attempt to protect faith by external ceremonies, which might easily lure a Roman Catholic or a Jew into finding parallels in Grundtvig to the sacraments or to circumcision, respectively. But what may be of interest abroad today is not his theological sectarianism. Rather, pointing to his psychology and anthropology, one may draw attention to the fact that, very early, Grundtvig had seen through the problems of intellectualism and individualism, and that he might profitably be compared with Martin Buber and Paul Ricoeur.H. Østergaard-Nielsen’s attempt to confront Kierkegaard and Grundtvig is doomed because of his lack of hermeneutic discipline. Kierkegaard is seen as a gnostic, subjectivist, sentimental pessimist, whose theology is interpreted as a rationalisation of his relations with his father and Regine Olsen. These prejudiced views reveal more about their author than about Kierkegaard. More successful is the author’s characterisation of the Grundtvig of 1825 as the spokesman of the living word, which ‘creates what it mentions’ and exists in all human communities. In the light of this aspect of Grundtvig, Kierkegaard’s conception of faith is criticised for not going beyond the view that faith is ‘a personal relationship to a picture of Christ . . . for in that case the dualism of human life is looked upon as a philosophical dualism between the temporal and the eternal, between matter and spirit, and therefore the demand for contemporaneity with Christ implies a demand to die away from natural human life’.— This may be so; but we should not forget that Christianity in this radical sense was not what Kierkegaard demanded from his contemporaries, but only that they should become aware of the distance between this form of Christianity and their own. It is to be hoped that the Germans have sufficient insight to see through Kierkegaard’s indirectness, subtleties, and his dialectics.Heinrich Buss’ article on humanity and existence is far more thoroughgoing. His picture of Kierkegaard and Grundtvig is extremely subtle, and his critique is founded upon real penetration. The account of Kierkegaard as an anti-intellectualist is somewhat anachronistic however: he leaves us in the awkward position of not being able to find a place for what is human in Christianity if this concept is analysed with theological rigour. Nevertheless, Grundtvig is the offensive paradox that remains both before and after Kierkegaard.Jytte Engberg gives an attractive account of the curriculum of a Danish folk high school, and Jørgen Kristensen writes about the Danish national church. In his preface Götz Harbsmeier outlines the theological situation in Denmark, emphasising the break between Løgstrup and Olesen Larsen within the theological school known as ‘ Tidehverv’. Løgstrup himself launches an attack against this movement because it distinguishes so sharply between faith and cognition that ‘taking its stand on Kierkegaard, it disregards as irrelevant the problems of today.’ Vol. II is a German version of Løgstrup’s ‘ Opgør med Kirkegaard’, with a few additional chapters on Bultmann and ‘ The ethical Demand’ by Løgstrup himself with an epilogue on existential theology. The reviewer does not approve of Løgstrup’s view on Kierkegaard, however. As far as he can see Kierkegaard’s writings are susceptible of so many interpretations that they should be regarded as a potential of understanding, and thus they can be understood only in a continuous dialogue, as far as possible taking into account his total philosophy. Løgstrup’s statement in the preface that he will disregard Kierkegaard’s other writings is equivalent to refusing to participate in that dialogue.Kierkegaard was addressing a public that had destroyed the concept of Christianity through reflection, and, accordingly, he had to use their own weapons against them. The Christian religion must be reformulated for reflective people in such a way that all concepts are seen in reflexion. And in Synspunktet for min Forfattervirksomhed he wisely defined all his endeavours as an attempt to do this. But side by side with his philosophical writings he published ‘ Opbyggelige Taler’ addressed to those to whom Christian faith was still a matter of course. Not only is he a split personality, but he is also aware of the cleavage; he neutralises it in humour, and, in his most felicitous moments, in something that comes close to what he understood by faith: the self that yields to something greater and more powerful.But Kierkegaard’s and Grundtvig’s message to us ought not to be limited to what they say about faith and cognition and the relations between God and man. The project suffers from a preoccupation with formal theology. The understanding of the two integrated personalities is lost.